Pengaruh Metode Isolasi Terhadap Komposisi Proksimat, Sifat Pasting dan Morfologi Pati Sekoi (Setaria italica (L)P. Bauv) Varietas Lokal Bengkulu: Pengaruh Metode Isolasi Terhadap Komposisi Proksimat, Sifat Pasting dan Morfologi Pati Sekoi (Setaria italica (L)P. Bauv) Varietas Lokal Bengkulu - Fitri Electrika Dewi Surawan; Eni Harmayani; Nurliyani Nurliyani; Djagal Wiseso Marseno (Universitas Bangka Belitung, 2021)
Several research on foxtail millet starch have been studied, but there is no recommended method for isolation of foxtail millet starch. In this study, isolation of Bencoolen foxtail millet starch, using sodium hidroxyde with 1x, 2x and 3x cycles, hexane-Sodium hydroxide treatment, and destilled water were done. The purpose of this study were to determine isolation method of Bencoolen foxtail millet starch which minimum impurities, pasting and morphological properties. This research was conducted with a randomized complete design with isolation method as a factor. The result of this study shown that method of starch isolation with NaOH 0.3% three cycle, produces the highest of starch and amylose content were 83.15% and 19.40%. The moisture, ash, protein, fat and crude fiber content of foxtail millet starch were 8.48%, 0.47%, 4.45%, 0.09%, and 0.21%, respectively. The gelatinization temperature, peak time, viscosity, and break down viscosity value of this starch were 78 oC, 7.6 minutes, 4228 cp, and 2738 cp, respectively. It has the highest brightness (L*), and polygonal shape of starch granule.